European Small Business Finance Outlook: December 2019 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2019)
This working paper provides an overview of the main markets relevant to the EIF. It starts by discussing the general market environment, then looks at the main aspects of equity finance and the markets for SME debt products, and, finally, it highlights important aspects of microfinance in Europe. A chapter on Fintech complements the analysis. Many thanks to the colleagues who reviewed the sections relevant to their area. The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by EIF's Research & Market Analysis and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330